2019
DOI: 10.2965/jwet.18-047
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Environmental DNA in Sediment at Different Temporal Scales in Nearshore Area of Tokyo Bay

Abstract: Environmental DNA (eDNA) is a non-invasive and less labor-intensive tool for biological survey. The advantages enable more frequent sampling work, but there is a lack of fundamental field data on the variation of eDNA in sediment in different timescales. We conducted a yearlong sampling at two marine parks of Tokyo Bay (Odaiba Marine Park and Kasai Marine Park) to investigate the temporal variation of sediment eDNA at scales of one year, one month and one tidal period. Grandidierella japonica, an indicator ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Tokyo Bay has receiving discharges from sewage treatment plants, road runoff, and agricultural runoff [25], and thus sediment in this area reportedly contains high levels of many anthropogenic chemicals such as metals [26] and polycyclic aromatic hydrocarbons [25]. G. japonica has been reported to be present in coastal zones of Tokyo Bay [27]. Second, the effects of sediment particle size distribution on 10-day amphipod survival and body length were examined using formulated sediment comprising quartz sand and kaolin.…”
Section: Introductionmentioning
confidence: 99%
“…Tokyo Bay has receiving discharges from sewage treatment plants, road runoff, and agricultural runoff [25], and thus sediment in this area reportedly contains high levels of many anthropogenic chemicals such as metals [26] and polycyclic aromatic hydrocarbons [25]. G. japonica has been reported to be present in coastal zones of Tokyo Bay [27]. Second, the effects of sediment particle size distribution on 10-day amphipod survival and body length were examined using formulated sediment comprising quartz sand and kaolin.…”
Section: Introductionmentioning
confidence: 99%
“…and kelps Saccharina spp., to the blue carbon assessment around Japan merits detailed investigation. In addition, the sediments of Hiroshima Bay were surveyed only once in our study, yet Wei et al [74] reported seasonal variations in fish-derived eDNA in the sediments of Tokyo Bay, which is a similar estuary to Hiroshima Bay. If annual surveys were conducted in Hiroshima Bay, it is possible that the results would differ from the present results.…”
Section: Application Of the Designed Qpcr System To Field Samplesmentioning
confidence: 95%
“…In addition, temperature alterations caused by seasonal changes will also affect the content of eDNA in samples. For example, Wei et al (2019) studied the variation over time of eDNA in sediments over periods of 1 year, 1 month and one tidal period, and found that eDNA content was higher in the warm season and lower in the cold season. Similarly, the concentration and distribution of eDNA can be influenced by spatial factors such as spatial dissipation of eDNA and the flow of the water column.…”
Section: Key Aspects and Challenges In Edna Monitoring Of Amphibiansmentioning
confidence: 99%